Issues in the economic development and utilization of EU funds in a disadvantaged sub-region of the Southern Great Plain region - Horváth, Péter (Applied Studies in Agribusiness and Commerce, 2012)
The development period between 2007 and 2013 had a historical significance for Hungary as the funds that were provided by the European Union and were supplemented by the domestic and public sectors naturally offered great possibilities for the country’s sub-statistical regions and regions to inspire their development and innovation. In order to use these funds efficiently it is essential to incorporate the developments into the area’s capabilities, to harmonize them and to increase the role of the sub-statistical regions and regions. This study ranks the sub-regions of the Southern Great Plain Region in terms of their economic characteristics and identifies the most disadvantageous ones. Using as an example a specific sub-region it determines the local effects of EU payments with the application of different statistical methods.